Antibody-dependent cellular cytotoxicity and neutralization of human immunodeficiency virus type 1 by high affinity cross-linking of gp41 to human macrophage Fc IgG receptor using bispecific antibody - Mabondzo, Aloïse; Boussin, François; Raoul, Hervé; Le Naour, Richard; Gras, Gabriel; Vaslin, Bruno; Bartholeyns, Jacques; Romet-Lemonne, Jean-Loup; Dormont, Dominique (Journal of General Virology, 1994)
Human monocytes/macrophages, which express Fc receptors for IgG are involved in human immunodeficiency virus type 1 (HIV-1) infection and pathogenesis. These receptors are known to mediate numerous immunological functions including cell-mediated killing and possibly targeting of HIV to the lysophagosome monocyte-derived macrophage (MDM) entry route for virus neutralization. To study both activities in HIV-1 infection, MDM FcγRI was specifically selected using bispecific antibody (Bs-Ab) containing whole human monoclonal antibody against gp41 and the Fab′ fragment of murine anti- FcγRI 22.2 antibody. Bs-Ab was found to mediate potent antibody-dependent cellular cytotoxicity and virus neutralization.